Phosphorylation of SRSF1 by SRPK1 regulates alternative splicing of tumor-related Rac1b - Gonçalves, Vânia (2014)
The pre-messenger RNA of the majority of human genes can generate various transcripts through alternative splicing, and different tissues or disease states show specific patterns of splicing variants. These patterns depend on the relative concentrations of the splicing factors present in the cell nucleus, either as a consequence of their expression levels or of post-translational modifications such as protein phosphorylation, which are determined by signal transduction pathways. Here we analyzed the contribution of protein kinases to the regulation of alternative splicing variant Rac1b that is overexpressed in certain tumor types. In colorectal cells we found that depletion of AKT2, AKT3, GSK3β and SRPK1 significantly decreased endogenous Rac1b levels. Whereas knockdown of AKT2 and AKT3 affected only Rac1b protein levels suggesting a post-splicing effect, the depletion of GSK3β or SRPK1 decreased Rac1b alternative splicing, an effect mediated through changes in splicing factor SRSF1. In particular, the knockdown of SRPK1 or inhibition of its catalytic activity reduced phosphorylation and subsequent translocation of SRSF1 to the nucleus, limiting its availability to promote the inclusion of alternative exon 3b into the Rac1 pre-mRNA. Altogether, the data identify SRSF1 as a prime regulator of Rac1b expression in colorectal cells and provide further mechanistic insights into how the regulation of alternative splicing events by protein kinases can contribute to sustain tumor cell survival.